Factor analysis of anthropometric characteristics in young swimmers age 11 and 12 - Ostrowska, B.; Domaradzki, J.; Ignasiak, Z. (Acta Universitatis Palackianae Olomucensis. Gymnica, 2006)
The aim of this study was to describe the set of somatic characteristics, which significantly discriminate young swimmers. The factor analysis let us reduce the number of somatic traits mostly correlated and to calculate the main structural factors typical for young swimmers. There were 80 pupils (11 and 12 years old) from the primary sport school in Wroclaw recruited for the study. The participants selected for the study had been involved in swimming for 2-3 years. On average their training time was 12 to 18 hours per week. The following parameters were established: body height and weight, upper and lower extremities` length, circumferences of: the thigh, shank, arm, forearm, chest at rest, chest after inspiration, chest after expiration, waist, hips, shoulder width, hips` width, chest width, chest depth, and Rohrer index. All data were normalised at mean and standard deviation to join all children in one group. In order to accomplish the aim of the study, a factor analysis method was employed. Analysis of the results indicated that only some traits, from among all data, are characteristic for young swimmers. They are connected into two somatic factors: the cubic content (including body weight, muscles, trunk and upper and lower extremities` circumferences), vertical dimension (including body height and upper and lower extremities` lengths). Those parameters indicate formation of the body figure typical for swimmers, characterised by specific proportions of the body`s weight and height, chest and hips, and usually by longer limbs. Results suggest those somatic parameters characterising young swimmers in the best way. They should be used in a training process` estimation and a check-up of after training changes, as well as sport selection.